Improving hand hygiene compliance in child daycare centres: a randomized controlled trial. Issue 12 (19th May 2016) - ZOMER, T. P.; ERASMUS, V.; LOOMAN, C. W.; VAN BEECK, E. F.; TJON-A-TSIEN, A.; RICHARDUS, J. H.; VOETEN, H. A. C. M.
SUMMARY: Gastrointestinal and respiratory infections in children attending daycare centres (DCCs) are common and compliance with hand hygiene (HH) guidelines to prevent infections is generally low. An intervention was developed to increase HH compliance and reduce infections in DCCs. The objective of this paper was to evaluate the effectiveness of this intervention on HH compliance. The intervention was evaluated in a two-arm cluster randomized controlled trial in 71 DCCs in The Netherlands. Thirty-six DCCs received the intervention including: (1) HH products; (2) training about HH guidelines; (3) two team training sessions aimed at goal setting and formulating HH improvement activities; and (4) reminders and cues for action (posters/stickers). Intervention DCCs were compared to 35 control DCCs that continued usual practice. HH compliance of caregivers and children was observed at baseline and at 1, 3 and 6 months follow-up. Using multilevel logistic regression, odds ratios (ORs) with 95% confidence intervals (CIs) were obtained for the intervention effect. Of 795 caregivers, 5042 HH opportunities for caregivers and 5606 opportunities for supervising children's HH were observed. At 1 month follow-up caregivers' compliance in intervention DCCs was 66% vs. 43% in control DCCs (OR 6·33, 95% CI 3·71–10·80), and at 6 months 59% vs. 44% (OR 4·13, 95% CI 2·33–7·32). No effect of the intervention was found on supervising children's HH (36% vs. 32%; OR 0·64, 95% CI 0·18–2·33). In conclusion, HH compliance of caregivers increased due to the intervention, therefore dissemination of the intervention can be considered.